2013
DOI: 10.1016/j.molcel.2013.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Bacterial Persistence by HipA

Abstract: HipA of Escherichia coli is a eukaryote-like serine-threonine kinase that inhibits cell growth and induces persistence (multidrug tolerance). Previously, it was proposed that HipA inhibits cell growth by the phosphorylation of the essential translation factor EF-Tu. Here, we provide evidence that EF-Tu is not a target of HipA. Instead, a genetic screen reveals that the overexpression of glutamyl-tRNA synthetase (GltX) suppresses the toxicity of HipA. We show that HipA phosphorylates conserved Ser(239) near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
330
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(339 citation statements)
references
References 42 publications
8
330
0
1
Order By: Relevance
“…TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 . Ectopic overexpression of ribonucleases (RelE and MazF toxin), HipA (a glutamyl transfer RNA synthetase protein kinase) and TisB (membrane damage protein) enhances drug tolerance in bacteria 39,[62][63][64] . In E. coli, TA systems function synergistically, and the successive deletion of 10 TA systems progressively reduces persister cell formation in vitro 8 .…”
Section: Discussionmentioning
confidence: 99%
“…TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 . Ectopic overexpression of ribonucleases (RelE and MazF toxin), HipA (a glutamyl transfer RNA synthetase protein kinase) and TisB (membrane damage protein) enhances drug tolerance in bacteria 39,[62][63][64] . In E. coli, TA systems function synergistically, and the successive deletion of 10 TA systems progressively reduces persister cell formation in vitro 8 .…”
Section: Discussionmentioning
confidence: 99%
“…HipA was first thought to phosphorylate the translation factor EF-Tu, leading to persistence via cell stasis (107). However, it was recently shown that HipA more likely inhibits glutamyl-tRNA synthetase (GltX) through phosphorylation and thus triggers the synthesis of ppGpp (see below) (108).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%
“…RelE inhibits translation by cleavage of ribosome-bound mRNAs at the ribosomal A site (20). HipA inhibits translation by phosphoryla-tion of glutamyl-tRNA synthetase (21). VapC toxins from some enteric bacteria cleave the initiator tRNA fMet (22).…”
mentioning
confidence: 99%